Alzheimer’s Disease Associated Genes Ankyrin and Tau Cause Shortened Lifespan and Memory Loss in Drosophila - Higham, James P.; Malik, Bilal R.; Buhl, Edgar; Dawson, Jennifer M.; Ogier, Anna S.; Lunnon, Katie; Hodge, James J. L. (Frontiers in Cellular Neuroscience, 2019)
Alzheimer’s disease (AD) is the most common form of dementia and is characterized by intracellular neurofibrillary tangles of hyperphosphorylated Tau, including the 0N4R isoform and accumulation of extracellular amyloid beta (ABeta) plaques. However less than 5% of AD cases are familial, with many addition risk factors contributing to AD including ageing, lifestyle, the environment and epigenetics. Recent epigenome-wide association studies (EWAS) of AD have identified a number of loci that are differentially methylated in the AD cortex. Indeed, hypermethylation and reduced expression of the Ankyrin 1 (ANK1) gene in AD has been reported in the cortex in numerous different post-mortem brain cohorts. Little is known about the normal function of ANK1 in the healthy brain, nor the role it may play in AD. We have generated Drosophila models to allow us to functionally characterize Drosophila Ank2, the ortholog of human ANK1 and to determine its interaction with human Tau and ABeta. We show expression of human Tau 0N4R or the oligomerizing ABeta 42 amino acid peptide caused shortened lifespan, degeneration, disrupted movement, memory loss and decreased excitability of memory neurons with co-expression tending to make the pathology worse. We find that Drosophila with reduced neuronal Ank2 expression have shortened lifespan, reduced locomotion, reduced memory and reduced neuronal excitability similar to flies overexpressing either human Tau 0N4R or ABeta42. Therefore, we show that the mis-expression of Ank2 can drive disease relevant processes and phenocopy some features of AD. Therefore, we propose targeting human ANK1 may have therapeutic potential. This represents the first study to characterize a gene implicated in AD, which was nominated from EWAS.